A review of the enzymes utilization in the feed for indigenous Indonesian fish : enzymes utilization in the feed for indigenous Indonesian fish - Maser, Wahyu Haryati; Muhtadi, Ahmad; Ritonga, Ajuan; Almira, Della; Panjaitan, Febriyanti; Sari, Nurmala; Sinurat, Ries Ruth Rytond; Kembaren, Natasyha Pebrina Br Sembiring; Purba, Theresia Widi Astuti; Nababan, David; Andari, Ella; Harahap, Muhamad Haikal Firyaldi; Pasaribu, Rihan Addilah (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2025)
Enzymes play a vital role in improving nutrient absorption and digestion efficiency in fish feed, particularly for indigenous Indonesian fish species. This review aimed to comprehensively evaluate the current state of enzyme utilization in feed for native Indonesian fish, highlighting its benefits, challenges, and potential contributions to the advancement of sustainable aquaculture. It examined the role of endogenous enzymes and various exogenous enzymes, such as protease, lipase, phytase, Non-Starch Polysaccharides (NSP) enzymes, and multi-carbohydrase complexes, in enhancing feed efficiency and fish growth. The integration of these enzymes into feed formulations offers significant advantages in boosting growth performance, optimizing feed conversion efficiency, and promoting environmental sustainability. Additionally, this review discussed the potential benefits and challenges associated with enzyme application in fish feed. Looking ahead, the development of enzyme utilization in aquafeed holds great promise for enhancing the sustainability, efficiency, and productivity of the aquaculture sector. This review provides valuable insights into the potential of enzyme supplementation to maximize feed utilization for native Indonesian fish species, outlining both its advantages and challenges, while also exploring its future prospects in driving cost-effective and eco-friendly aquaculture practices.